SERTIFIKASI HALAL SEBAGAI UPAYA PENGEMBANGAN UMKM ROTI GAPLEK DI KABUPATEN WONOGIRI (Studi Kasus Pada Roti Gaplek Inagiri) - Choirul Amir (Inisiasi, 2023)
This research aims to determine the impact of halal certification on the development of Inagiri Cassava Bread UMKM products in Wonogiri Regency. This research is field research with a qualitative approach. Data collection techniques using interviews, observation and literature study. The results of this research show that halal certification is an important part of people's interest and trust in consuming it. This is proven by the increase and development of MSME business products, namely Inagiri Gaplek Roti. Inagiri Cassava Bread experienced an increase of around 45% after having legal halal certification. Another positive impact of halal certification is that Roti Gaplek Inagiri became the representative of Central Java in halal food at the sharia economic festival in Surabaya in 2019.